2023
DOI: 10.18502/ijps.v18i2.12370
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempt and Suicide Death in Iran: A Systematic Review and Meta-Analysis Study

Abstract: Objective: suicide attempts and suicide death fall within a category of psychological disorders that is under the influence of economic, social, and cultural factors. Awareness of the prevalence of this phenomenon is essential for the adoption of preventive policies. Accordingly, the current study was carried out in order to determine the prevalence of suicide attempts and suicide deaths via Meta-analysis in Iran. Method: This study is a systematic review and meta-analysis of articles published between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Similarly, in the study of Razai et al, the rate of suicide showed an increasing trend in Iranian elderly 17 . In a systematic review and meta-analysis of articles published between 2010 and 2021 in Iran, although Iran was ranked with a low prevalence of suicide attempts and suicide deaths compared to the world average, however, the trend of suicide attempts was increasing and mostly affecting young people 2 . Unlike our study, the results of this systematic review study showed that the trend of suicide deaths was decreasing 2 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, in the study of Razai et al, the rate of suicide showed an increasing trend in Iranian elderly 17 . In a systematic review and meta-analysis of articles published between 2010 and 2021 in Iran, although Iran was ranked with a low prevalence of suicide attempts and suicide deaths compared to the world average, however, the trend of suicide attempts was increasing and mostly affecting young people 2 . Unlike our study, the results of this systematic review study showed that the trend of suicide deaths was decreasing 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is one of the main causes of unnatural death in the world 1 . Suicide is defined by World Health Organization (WHO), as an act in which a person hurts himself/herself consciously and without the intervention of others 2 . The increased incidence of suicides in recent years has attracted widespread national and international attention 2 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations